Analisis Akad Pembiayaan Murabahah di Bank Syariah Indonesia Cabang Pringsewu - Sandi Irawan; Muhammad Iqbal Fasa; A. Kumedi Ja’far (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Islam as ad-din contains comprehensive and perfect teachings. Islam regulates all aspects of human life, not only aspects of worship, but also aspects of muamalah, especially sharia economics. The Islamic economic system has developed along with the advancement of science and technology. One form of embodiment of the Islamic economic system is the establishment of Islamic financial institutions in the form of banks and non-banks. The role and position of Islamic financial institutions is considered very important, especially in the development of a people's economic system. This is because the priority of Islamic financial institutions is more focused on forming stronger economic fundamentals.